2015
DOI: 10.1111/tmi.12541
|View full text |Cite
|
Sign up to set email alerts
|

The role of point‐of‐care tests in antibiotic stewardship for urinary tract infections in a resource‐limited setting on the Thailand–Myanmar border

Abstract: ObjectivePublished literature from resource‐limited settings is infrequent, although urinary tract infections (UTI) are a common cause of outpatient presentation and antibiotic use. Point‐of‐care test (POCT) interpretation relates to antibiotic use and antibiotic resistance. We aimed to assess the diagnostic accuracy of POCT and their role in UTI antibiotic stewardship.MethodsOne‐year retrospective analysis in three clinics on the Thailand–Myanmar border of non‐pregnant adults presenting with urinary symptoms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“… 34 , 71 , 72 An additional investigation showed that the concurrent use of two point-of-care rapid tests (urine dipstick and microscopy) improved antimicrobial prescribing in adults with urinary tract infections at the Thailand–Myanmar border. 73 …”
Section: Solutions To the Crisis: Surveillance Diagnostics Stewardsmentioning
confidence: 99%
“… 34 , 71 , 72 An additional investigation showed that the concurrent use of two point-of-care rapid tests (urine dipstick and microscopy) improved antimicrobial prescribing in adults with urinary tract infections at the Thailand–Myanmar border. 73 …”
Section: Solutions To the Crisis: Surveillance Diagnostics Stewardsmentioning
confidence: 99%
“…Despite proper guidance on using the dipstick test result in a rule-out strategy for UTI, over 50% of participants with UTI-associated symptoms but with a negative dipstick result were prescribed antibiotics. 17 …”
Section: Discussionmentioning
confidence: 99%
“…24 Another study at the Thailand-Myanmar border found that in a population largely comprised of migrants and refugees, combined pointof-care testing of urinary tract infections (urine dipstick and microscopy together) improved appropriate antimicrobial prescribing, showing the use of only one test (urine dipstick or urine microscopy alone versus both tests combined when compared to urine culture as the gold standard) to be ineffective in the setting of high prevalence of multidrug resistance in the area. 25 A qualitative, cross-sectional study in which Palestinian refugees at Jordanian refugee camps were interviewed revealed high prevalence of inappropriate antibiotic use, poor knowledge base of antibiotic side effects and resistance, and long wait times to see providers, preventing refugees from seeking medical advice. 26 Most inappropriate use was attributed to over-thecounter acquisition of antibiotics without a prescription and self-medication at home or the use of leftover antibiotics from social contacts.…”
Section: Existing Evidencementioning
confidence: 99%